العُرف: دراسة أصولية اجتماعية: Custom: A Socio-Usuli study - صوالحي يونس; بوهدة غالية (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2015)
تتناول هذه الدراسة موضوع العُرف بوصفه قوّةً مُؤثِّرةً في بناء المجتمعات الإنسانية وتنميتها، وتبحث بمنهج تحليلي مقارن أهم ما انتهت إليه المعارف الإنسانية -سواء ما استند منها إلى مرجعية الوحي (القرآن والسنّة) وذلك عند المجتهدين الأصوليين، أو ما استند إلى المرجعية الوضعية كما يرى علماء القانون والاجتماع- في تفسيرها لنشأة الأعراف وتطوّرها، وإيجاد أدوات منهجية مناسبة في دراستها، وفي استكشاف القوانين الاجتماعية الحاكمة في ذلك؛ لغرض تسخيرها في تنمية المجتمعات على نحوٍ تتكامل فيه بين حاجاتها المادية ومتطلّباتها الروحية. This study addresses the concept of custom as an influential factor in building and developing human societies. Using comparative-analytical research methods, it examines both revealed knowledge (Qur'an and Sunnah) of Muslim Usuli jurists and positivistic knowledge propagated by contemporary scholars of law and sociology in relation to the emergence and development of customs. It also aims at finding methodological instruments, and discovering the governing social laws necessary to develop societies both physically and spiritually.